Short‐term hypoxia promotes vascularization in co‐culture system consisting of primary human osteoblasts and outgrowth endothelial cells. Issue 1 (17th September 2019) - Ma, Bin; Li, Ming; Fuchs, Sabine; Bischoff, Iris; Hofmann, Alexander; Unger, Ronald E.; Kirkpatrick, Charles J.
Abstract: Prevascularization of tissue constructs before implantation has been developed as a novel and promising concept for successful implantation. Since hypoxia might induce angiogenesis, we have investigated the effects of hypoxic treatment on vascularization by using co‐cultures of primary human osteoblasts (POBs) and outgrowth endothelial cells. Our results show that: (a) repeated short‐term hypoxia (2% O2 for 8 hr), not long‐term hypoxia (2% O2 for 24 hr), over 1 or 2 weeks, significantly enhances microvessel formation in co‐cultures; (b) sustained hypoxia, not short‐term or long‐term hypoxia, causes cytotoxicity in mono‐ and co‐cultures; (c) the expression of some angiogenic and inflammatory factors such as vascular endothelial growth factor, platelet‐derived growth factor subunit B, insulin‐like growth factor 1, interleukin‐8, and early growth response protein 1 increases significantly in hypoxia‐treated POB monoculture and co‐cultures after single or multiple 8‐ or 24‐hr hypoxic treatments; (d) long‐term (24 hr) hypoxic treatment induces more angiogenic inhibitors compared with short‐term hypoxic treatment. Our findings suggest that hypoxia‐induced vascularization/angiogenesis is regulated by a complex balance of angiogenic/antiangiogenic factors, and that repeated short‐term hypoxia, but not repeated long‐term hypoxia, promotes the vascularization and tissue regeneration of bone tissue constructs.